Efeitos da cirurgia bariátrica sobre a pressão arterial e a modulação autonômica cardíaca em obesos metabolicamente saudáveis e com doenças crônicas não transmissíveis: um acompanhamento de curto prazo - Santos, Karla Thuany de Oliveira (2021)
Obesity is linked to disorders of the autonomic nervous system (ANS), with repercussions on the overactivation of the sympathetic nervous system (SNS) and depression of the parasympathetic nervous system (SNP). Bariatric surgery (CB) appears as an important alternative for the treatment of obesity and regulation of the ANS. Thus, this study aimed to investigate short-term changes in anthropometric parameters, body composition, blood pressure and heart rate variability (HRV) in metabolically healthy obese individuals or those associated with chronic disease undergoing CB. It was a longitudinal study composed of 27 individuals belonging to the outpatient clinic of CB of the University Hospital Lauro Wanderley, João Pessoa-PB, carried out between March and September 2018. Participants were allocated into two groups: metabolically healthy obese (WHO, n = 11) and obese associated with chronic disease (OADC, n = 16). Body mass index (BMI), trunk fat, body fat percentage (BFP), systolic blood pressure (SBP), diastolic blood pressure (DBP) were evaluated. Linear and non-linear HRV parameters and heart rate were also evaluated by electrocardiogram. All data were assessed at baseline and 4 weeks after performing vertical gastrectomy or Roux-en-Y gastric bypass. Participants were composed of 27 individuals (23 women and 4 men), with an average age of 32.1 years ± 5.3; Weight of 112.2 kg ± 19.1 and BMI: 43.9 kg / m² ± 4.4 in the WHO group. The average age of the OADC group was 44.8 years; Weight: 104.6 kg ± 8.4 and BMI: 40.8 kg / m² ± 3.7. Among the most performed procedure of CB, was Roux-En-Y Gastric Bypass in both groups, with percentages of 54.5% and 75% respectively. After four weeks after CB, participants in both groups showed a reduction in body weight, BMI, SBP, DBP and HR (p <0.05). At baseline, individuals in the OACD group had impaired HRV in the time and frequency domain compared to the WHO group (p <0.05). HRV in the WHO group was not changed after four weeks of CB (p> 0.05). However, individuals in the OADC group had increased HRV indices after CB (p < 0.05). In view of the above, it was concluded that CB is an effective treatment to promote a reduction in blood pressure and HR in obese individuals with or without metabolic syndrome. Furthermore, the data demonstrated that BC was more effective in improving cardiac autonomic modulation in the OADC group.